The relationship between the number of repetitions performed at given intensities is different in endurance and strength trained athletes - Richens, B.; Cleather, D. J. (Biology of Sport, 2014)
Prescribing training intensity and volume is a key problem when designing resistance training programmes. One approach is to base training prescription on the number of repetitions performed at a given percentage of repetition maximum due to the correlation found between these two measures. However, previous research has raised questions as to the accuracy of this method, as the repetitions completed at different percentages of 1RM can differ based upon the characteristics of the athlete. The objective of this study was therefore to evaluate the effect of population characteristics on the relationship between the load lifted (as a percentage of one repetition maximum) and the number of repetitions achieved. Eight weightlifters and eight endurance runners each completed a one repetition maximum test on the leg press and completed repetitions to fatigue at 90, 80 and 70% of their one repetition maximum. The endurance runners completed significantly more repetitions than the weightlifters at 70% (39.9 ± 17.6 versus 17.9 ± 2.8; p < 0.05) and 80% (19.8 ± 6.4 versus 11.8 ± 2.7; p < 0.05) of their one repetition maximum but not at 90% (10.8 ± 3.9 versus 7.0 ± 2.1; p > 0.05) of one repetition maximum. These differences could be explained by the contrasting training adaptations demanded by each sport. It is important that practitioners should consider population specific characteristics when prescribing training loads based upon the number of repetitions to be completed at a given percentage of 1RM.